The Influence of Parenting Style, Achievement Motivation and Self-Regulation on Academic Achievement - et. al., Cucu Sopiah, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This study aimed to empirically prove the variables of parenting style, achievement motivation, and self-regulation on academic achievement. Data were collected employing cluster random sampling to second-grade elementary school students in Cirebon Regency. The results revealed that parenting style, achievement motivation, and self-regulation partially influenced academic achievement. Not only partially, but academic achievement was also indirectly influenced by parenting style and achievement motivation mediated by self-regulation. This study provides a scientific contribution that academic achievement will be better if parents have a role related to positive parenting style. Not only that, but students are also assisted and motivated related to the desire to have an achievement mediated by self-regulation.